2022
DOI: 10.1007/s00423-022-02467-y
|View full text |Cite
|
Sign up to set email alerts
|

Textbook outcome after major hepatectomy for perihilar cholangiocarcinoma — definitions and influencing factors

Abstract: Purpose The concept of “textbook outcome” (TO) as composite quality measure depicting the ideal surgical has not yet been defined for patients undergoing major hepatectomy (MH) for perihilar cholangiocarcinoma (PHC). This study sought to propose a uniform definition through a systematic literature review as well as to identify patient- or procedure-related factors influencing TO. Methods In this retrospective study, we analyzed all patients undergoing MH f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…These data are very interesting, but need to be considered in a larger overall context. Overall short-and long-term outcomes are well in line with previous analyses (8,11,12). However, some points differ from previous analyses.…”
supporting
confidence: 86%
“…These data are very interesting, but need to be considered in a larger overall context. Overall short-and long-term outcomes are well in line with previous analyses (8,11,12). However, some points differ from previous analyses.…”
supporting
confidence: 86%
“…TOs for patients with cholangiocarcinoma have been found to be worse than the general population of hepatectomy patients, as Merath et al 11 reported that only 25.5% of patients who underwent liver resection for intrahepatic cholangiocarcinoma achieved a TO, but their dropout rate was significantly influenced by prolonged hospital stay, which we did not include among the criteria of a TO. Benzing et al 23 also reported a low rate of TO in 24% of patients who underwent major hepatectomy for perihilar cholangiocarcinoma and they found that right hepatic lobectomy patients had a lower chance to achieve a TO compared with left hepatectomy. Finally, the laparoscopic approach to right hepatic lobectomy seems to be associated with a significantly lower chance to achieve a TO, as Hobeika et al 17 reported a 23.8% rate of TO, which is approximately half of the TO rate of the open approach, as reported by us in this study and Tsilimigras et al 12 previously.…”
Section: Discussionmentioning
confidence: 98%
“…We selected these 7 parameters based on studies published in the literature, and also based on what we felt were most clinically meaningful. [9][10][11][12]17,[22][23][24] For example, we did not use ICU LOS as a criterion, as all of the live donor right hepatectomy cases are routinely admitted to the ICU in our institution, while the cancer patients are admitted selectively. Instead, we selected the measure of an urgent unplanned postoperative transfer (eg, condition "C") from the floor to the ICU as a failure of a TO, as that indicates a clinical deterioration of the patient who requires ICU care.…”
Section: Definition Of Tosmentioning
confidence: 99%
“…Among them, radical resection (21 months) was significantly better than palliative resection (13.8 months) and palliative biliary drainage (8.7 months) in median survival, which is the same as other studies. [19][20][21] Because Bismuth-Corlette typing is simple to operate, it is widely used in clinical practice to guide surgical treatment, improve R0 resection rate, and achieve the purpose of prolonging survival. However, some foreign scholars used the Bismuth-Corlette typing criteria to classify 230 patients with resectable HCCA.…”
Section: Discussionmentioning
confidence: 99%